RPC-based Muon Identification System for the neutrino detector of the SHiP experiment. (24th February 2023) - Albanese, R.; Alexandrov, A.; Buontempo, S.; Choi, K.-Y.; Congedo, L.; de Asmundis, R.; De Lellis, G.; de Magistris, M.; De Robertis, G.; De Serio, M.; Debernardis, F.; Di Crescenzo, A.; et al.
Abstract: The SHiP experiment has been proposed at CERN to shed light on phenomena still unexplained in the framework of the Standard Model, such as the nature of dark matter, the baryonic asymmetry of the Universe and the neutrino oscillations, searching for hints of New Physics. A section of the detector will be dedicated to the study of neutrino physics with special emphasis on tau neutrino properties, still very poorly measured. A system to identify the muons produced in neutrino interactions, based on RPC technology, has been proposed and it is presented in detail in this paper.